Romeo and Juliet, from Page to Stage and Back: A Hands-On Perspective on Functionalism in Drama Translationi - Ignat Anca-Diana (American, British and Canadian Studies Journal, 2023)
A decade ago I translated Romeo and Juliet into Romanian for a student performance, which premiered on February 14, 2013 and has since participated in four international theatre festivals. Three years later, having joined the team of the Shakespeare for the New Millennium project – devoted to the retranslation of Shakespeare’s complete works – I embarked on what I thought would be merely a revision of my previous translation for the stage, but soon turned into a very different translatorial experience, which resulted in an entirely new Romanian version, mainly due to the twofold, yet more clearly defined purpose of the translation project. This new version, published in vol. 13 (2018) of the latest scholarly edition of Shakespeare’s complete works (2010-2019), has recently passed the performability test as well, in a compelling stage production which premiered, to great acclaim, on December 17, 2022 at the “Mihai Eminescu” National Theatre in Chișinău (Moldova). Thus, my article sets out to explore – self-reflectively, retrospectively and through the lens of Skopos theory – how in each case my approach to the task in hand, my decisions and my solutions to various translation problems were guided by what I knew or assumed about the aims, requirements and prospective audience of each translation. Thus, a translator’s practical experience is brought to bear on what has been both hailed and criticised as “a new paradigm” in translation studies, in an attempt to test its hypotheses against the actual practice (as well as the outcomes) of translating the same text for different purposes.